Intelligent Computing for Sustainable Energy and Environment Second International Conference, ICSEE 2012, Shanghai, China, September 12-13, 2012. Revised Selected Papers - Li, Kang.; Li, Shaoyuan; Li, Dewei; Niu, Qun.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the Second International Conference on Intelligent Computing for Sustainable Energy and Environment, ICSEE 2012, held in Shanghai, China, in September 2012. The 60 full papers presented were carefully reviewed and selected from numerous submissions and present theories and methodologies as well as the emerging applications of intelligent computing in sustainable energy and environment.
Study on Controlling Power Quality Based on Thermodynamics Modeling Method for 6.3kV Power System -- Recursive Model Predictive Control for Fast Varying Dynamic Systems -- Distributed Optimization and State Based Ordinal Potential Games -- Assessment of Texaco Syngas Components Using Extreme Learning Machine Based Quantum Neural Network -- Stochastic Gradient Algorithm for Hammerstein Systems with Piece-Wise Linearities -- Optimization of Train Energy-Efficient Operation Using Simulated Annealing Algorithm -- Artificial Cobweb Intelligent Routing Algorithm for Low-Voltage Power Line Communication -- Material Identification of Particles in Space-Borne Electronic Equipments Based on Principal Component Analysis -- Research and Application of Multiple Model Predictive Control in Ultra-supercritical Boiler-Turbine System -- A Decision Support Framework for Collision Avoidance of Unmanned Maritime Vehicles.
Keywords: Computer science; Computer software; Electronic data processing; Data mining; Artificial intelligence; Optical pattern recognition; Computer Science; Computer Applications; Data Mining and Knowledge Discovery; Algorithm Analysis and Problem Complexity; Numeric Computing; Artificial Intelligence (incl. Robotics).; Pattern Recognition